Unravelling the impact of SARS-CoV-2 on hemostatic and complement systems: a systems immunology perspective - Murad, Didar; Paracha, Rehan Zafar; Nisar, Maryum (Frontiers in Immunology, 2025)
The hemostatic system prevents and stops bleeding, maintaining circulatory integrity after injury. It directly interacts with the complement system, which is key to innate immunity. In coronavirus disease 2019 (COVID-19), dysregulation of the hemostatic and complement systems has been associated with several complications. To understand the essential balance between activation and regulation of these systems, a quantitative systems immunology model can be established. The dynamics of the components are examined under three distinct conditions: the disease state representing symptomatic COVID-19 state, an intervened disease state marked by reduced levels of regulators, and drug interventions including heparin, tranexamic acid, avdoralimab, garadacimab, and tocilizumab. Simulation results highlight key components affected, including thrombin, tissue plasminogen activator, plasmin, fibrin degradation products, interleukin 6 (IL-6), the IL-6 and IL-6R complex, and the terminal complement complex (C5b-9). We explored that the decreased levels of complement factor H and C1-inhibitor significantly elevate these components, whereas tissue factor pathway inhibitor and alpha-2-macroglobulin have more modest effects. Furthermore, our analysis reveals that drug interventions have a restorative impact on these factors. Notably, targeting thrombin and plasmin in the early stages of thrombosis and fibrinolysis can improve the overall system. Additionally, the regulation of C5b-9 could aid in lysing the virus and/or infected cells. In conclusion, this study explains the regulatory mechanisms of the hemostatic and complement systems and illustrates how the biopathway machinery sustains the balance between activation and inhibition. The knowledge that we have acquired could contribute to designing therapies that target the hemostatic and complement systems.